2021
DOI: 10.1016/j.jasrep.2021.103080
|View full text |Cite
|
Sign up to set email alerts
|

Pottery use in the mining site of variscite Mines de Gavà (Barcelona, Spain) during the 4th millennium BC based on organic residue analysis

Abstract: Residue analysis in pottery usually concerns habitat or funerary sites. In this work, we have studied 21 vases from the Mines of Gavà (Barcelona, Spain) which constitute the oldest evidence of mining focused on variscite during the IV th millennium BC. The main objectives are determining the degree of preservation of lipids in this context, identifying the natural substances exploited in the vessels and highlighting pottery use in the day-today mining work at this site, as well as establishing if some of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Beehive products, such as beeswax, are known from other Iron Age contexts [ 24 , 34 , 88 , 89 ], and earlier periods [ 90 ]. It is a substance previously associated with waterproofing [ 69 , 88 ] or interpreted as fuel for lamps [ 78 , 91 ], and mixtures with birch tar for repair, decoration and vessel coatings are known [ 16 , 24 ]. Beeswax has often been referred to as a plasticising agent and experimental studies on mixtures of pine rosin and beeswax demonstrated that adhesive strength can be enhanced through mixing [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beehive products, such as beeswax, are known from other Iron Age contexts [ 24 , 34 , 88 , 89 ], and earlier periods [ 90 ]. It is a substance previously associated with waterproofing [ 69 , 88 ] or interpreted as fuel for lamps [ 78 , 91 ], and mixtures with birch tar for repair, decoration and vessel coatings are known [ 16 , 24 ]. Beeswax has often been referred to as a plasticising agent and experimental studies on mixtures of pine rosin and beeswax demonstrated that adhesive strength can be enhanced through mixing [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…hircus individuals (MNI = 3 out of 8) may suggest the cave was utilised as a stable and/or breeding area [ 39 ]. The exploitation of dairy was further confirmed by milk residues documented in ceramic pots [ 40 ]. Taphonomic analyses also reveal a significant number of remains with alterations due to their deposition in manure, which may be related to the cohabitation of animals and humans in the same space [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Organic residue analysis was carried out on eight ceramic vessels found on the upper floor of the building (Tarifa-Mateo et al, 2021). Most of them were handmade cooking vessels.…”
Section: Residue Analysismentioning
confidence: 99%